Old dogs [videorecording (DVD)] - Diamond, David, 1965-; Weissman, David; Travolta, John, 1954-; Williams, Robin, 1951-2014; Preston, Kelly; Green, Seth, 1974-; Dillon, Matt (Disney DVD., 2010)
Dan and Charlie are two best friends who, together, have built a successful marketing empire, but have somehow managed to avoid ever really growing up. Their lives are turned upside down when they are charged with the care of seven-year-old twins while on the verge of a big business deal. The clueless bachelors stumble in their efforts, leading to one debacle after another, with a gorilla and some pecking penguins. Dan and Charlie learn as much from the kids as vice versa.